Stochastic Crystal Plasticity Models with Internal Variables: Application to Slip Channel Formation in Irradiated Metals - Zaiser, Michael; Moretti, Paolo; Chu, Haijan (Advanced Engineering Materials, 2019)
Stochastic crystal plasticity models are originally introduced to study slip avalanche phenomena that are ubiquitous features of the microscale plasticity of crystalline solids. Herein, a method is proposed to couple such models to the evolution of internal variables to account for microstructural hardening and softening phenomena. Specifically, strain hardening is described in terms of a Kocks-Mecking-type dislocation density and the structural softening of irradiated metals in terms of the density of irradiation-induced point defect agglomerates, which are cut and eliminated by moving dislocations. The interplay of both effects results in the formation of defect-free slip channels. Critical conditions for slip channel formation are formulated, the statistical morphology of the ensuing slip channel patterns is investigated and compared with surface observations. Finally, the magnitude and nature of stress concentrations that emerge if slip channels interact with platelet-like hard inclusions are discussed.
CRIS-Team WoS Importer:2019-12-27